Quantifying Brexit: From Ex Post to Ex Ante Using Structural Gravity - Gabriel Felbermayr; Jasmin Katrin Gröschl; Marina Steininger (Center for Economic Studies and ifo Institute (CESifo), 2018)
Exploiting changes in the geography of economic integration in Europe, this paper uses detailed bilateral trade data for 50 sectors to carry out an econometric ex post evaluation of the trade cost effects of the United Kingdom's various arrangements with the European Union. The analysis reveals important heterogeneity across agreements, sectors, and within pairs. In particular, the EU's eastward enlargement or the EU-Korea trade agreement have lowered the UK's outward trade costs only relatively modestly. These asymmetries matter for the size and distribution of the welfare effects of Brexit – the withdrawal of the UK from EU agreements resulting into a return of trade costs to the situation quo ante. We make this point with the help of a modern multi-sector trade model that is able to capture inter- and intranational production networks. In line with other papers, the welfare costs of Brexit are higher in the UK than in most other EU countries. However, the considered asymmetries tend to attenuate overall costs while giving rise to substantial heterogeneity between EU27 members and sectors.
Keywords: F15; F17; N74; 330; structural gravity; European trade integration; general equilibrium; quantitative trade models; Brexit